WHO SHOULD BEAR THE ONUS IN RESTRAINT OF TRADE DISPUTES? Canoa KwaZulu-Natal (Pty) Ltd t/a Canon Office Automation v Booth 2004 1 BCLR 39 (N) - Mark Tait (Obiter, 2022)
Canoa Kwazulu-Natal (Pty) Ltd t/a Canon Office Automation v Booth (2004 1 BCLR 39 (N), hereafter “the Canon case”) was reported only in 2004 although the judgment had already been handed down on 27 March 2000. The matter before the court concerned the issue of restraint of trade provisions in the light of a constitutionally protected right to freedom of trade as provided for in section 22 of the Constitution of the Republic of South Africa (Act 108 of 1996, hereafter “the Constitution”). Of particular interest is the decision of the court as to who bears the burden of proof in a restraint of trade dispute. It is this aspect that forms the focus of this note.